2015
DOI: 10.1021/acs.jmedchem.5b00621
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Peripheral Carboxylates to Decrease the Charge on Tm3+ DOTAM-Alkyl Complexes: Implications for Detection Sensitivity and in Vivo Toxicity of PARACEST MRI Contrast Agents

Abstract: A series of structurally modified Tm(3+) DOTAM-alkyl complexes as potential PARACEST MRI contrast agents has been synthesized with the aim to decrease the overall positive charge associated with these molecules and increase their biocompatibility. Two types of structural modification have been performed, an introduction of terminal carboxylate arms to the alkyl side chains and a conjugation of one of the alkyl side chains with aspartic acid. Detailed evaluation of the magnetic resonance imaging chemical exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The [TmL 3 ] complex presents a better defined CEST feature at ∼−50 ppm that is well-defined at both 25 and 37 °C, regardless of the saturation power applied. This chemical shift is similar to those observed for Tm 3+ -DOTA tetraamide complexes …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The [TmL 3 ] complex presents a better defined CEST feature at ∼−50 ppm that is well-defined at both 25 and 37 °C, regardless of the saturation power applied. This chemical shift is similar to those observed for Tm 3+ -DOTA tetraamide complexes …”
Section: Resultssupporting
confidence: 86%
“…This chemical shift is similar to those observed for Tm 3+ -DOTA tetraamide complexes. 44 The CEST properties of the [TmL 2 ] + and [TmL 1 ] complexes were also investigated under analogous conditions (Table 3; see also Figure S25). The [TmL 1 ] complex presents the CEST properties comparable to those of [TmL 3 ], providing a CEST peak at a similar frequency.…”
mentioning
confidence: 99%
“…The authors showed that this complex can be observed in the kidneys of live mice after injection of a 0.4 mmol/kg dose. A second study on Ln­(III) PARACEST agents by Hudson and co-workers reported on related Tm­(III) complexes of DOTA tetramide complexes . These complexes display amide proton-based CEST and, in certain cases, feature dipeptide-functionalized pendent groups.…”
Section: Water Exchange Rotation and Mri Efficiencymentioning
confidence: 99%
“…A second study on Ln(III) PARACEST agents by Hudson and co-workers reported on related Tm(III) complexes of DOTA tetramide complexes. 16 These complexes display amide proton-based CEST and, in certain cases, feature dipeptide-functionalized pendent groups. The study from Hudson and his team targeted further functionalization of the amide pendent groups with peripheral carboxylate or aspartic acid groups to decrease the overall positive charge of the complexes and increase their biocompatibility.…”
mentioning
confidence: 99%
“…The L-lysine conjugated agent 10 displayed temperature-and pH-dependent CEST effects in the physiological range. Based on similarity to the analogous DOTAM-based agent, it is expected to have reasonable biocompatibility 39 and may be suitable for future in vivo Examination of the Yb 3+ complexes for DOTMAM, DOTMAM-Bn and DOTMAM-t-Bu indicated an overwhelming predominance of a single coordination isomer in solution although the t-butyl amide appeared different than the other two. The Tm 3+ complexes of these ligands also show the greatest difference in the chemical shift of the amide-proton CEST signal.…”
Section: Discussionmentioning
confidence: 99%